Angiotensin-converting-enzyme inhibitors and angiotensin receptor blockers for preventing the progression of diabetic kidney disease - Natale, Patrizia; Palmer, Suetonia C; Navaneethan, Sankar D; Craig, Jonathan C; Strippoli, Giovanni Fm (Cochrane database of systematic reviews, 2024)
Guidelines suggest that adults with diabetes and kidney disease receive treatment with angiotensin-converting-enzyme inhibitors (ACEi) or angiotensin receptor blockers (ARB). This is an update of a Cochrane review published in 2006. We compared the efficacy and safety of ACEi and ARB therapy (either as monotherapy or in combination) on cardiovascular and kidney outcomes in adults with diabetes and kidney disease. We searched the Cochrane Kidney and Transplants Register of Studies to 17 March 2024 through contact with the Information Specialist using search terms relevant to this review. Studies in the Register are identified through searches of CENTRAL, MEDLINE, and EMBASE, conference proceedings, the International Clinical Trials Registry Platform (ICTRP) Search Portal, and ClinicalTrials.gov. We included studies evaluating ACEi or ARB alone or in combination, compared to each other, placebo or no treatment in people with diabetes and kidney disease. Two authors independently assessed the risk of bias and extracted data. Summary estimates of effect were obtained using a random-effects model, and results were expressed as risk ratios (RR) and their 95% confidence intervals (CI) for dichotomous outcomes and mean difference (MD) or standardised mean difference (SMD) and 95% CI for continuous outcomes. Confidence in the evidence was assessed using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach. One hundred and nine studies (28,341 randomised participants) were eligible for inclusion. Overall, the risk of bias was high. Compared to placebo or no treatment, ACEi may make little or no difference to all-cause death (24 studies, 7413 participants: RR 0.91, 95% CI 0.73 to 1.15; I = 23%; low certainty) and with similar withdrawals from treatment (7 studies, 5306 participants: RR 1.03, 95% CI 0.90 to 1.19; I = 0%; low certainty). ACEi may prevent kidney failure (8 studies, 6643 participants: RR 0.61, 95% CI 0.39 to 0.94; I = 0%; low certainty). Compared to placebo or no treatment, ARB may make little or no difference to all-cause death (11 studies, 4260 participants: RR 0.99, 95% CI 0.85 to 1.16; I = 0%; low certainty). ARB have uncertain effects on withdrawal from treatment (3 studies, 721 participants: RR 0.85, 95% CI 0.58 to 1.26; I = 2%; low certainty) and cardiovascular death (6 studies, 878 participants: RR 3.36, 95% CI 0.93 to 12.07; low certainty). ARB may prevent kidney failure (3 studies, 3227 participants: RR 0.82, 95% CI 0.72 to 0.94; I = 0%; low certainty), doubling of serum creatinine (SCr) (4 studies, 3280 participants: RR 0.84, 95% CI 0.72 to 0.97; I = 32%; low certainty), and the progression from microalbuminuria to macroalbuminuria (5 studies, 815 participants: RR 0.44, 95% CI 0.23 to 0.85; I = 74%; low certainty). Compared to ACEi, ARB had uncertain effects on all-cause death (15 studies, 1739 participants: RR 1.13, 95% CI 0.68 to 1.88; I = 0%; low certainty), withdrawal from treatment (6 studies, 612 participants: RR 0.91, 95% CI 0.65 to 1.28; I = 0%; low certainty), cardiovascular death (13 studies, 1606 participants: RR 1.15, 95% CI 0.45 to 2.98; I = 0%; low certainty), kidney failure (3 studies, 837 participants: RR 0.56, 95% CI 0.29 to 1.07; I = 0%; low certainty), and doubling of SCr (2 studies, 767 participants: RR 0.88, 95% CI 0.52 to 1.48; I = 0%; low certainty). Compared to ACEi plus ARB, ACEi alone has uncertain effects on all-cause death (6 studies, 1166 participants: RR 1.08, 95% CI 0.49 to 2.40; I = 20%; low certainty), withdrawal from treatment (2 studies, 172 participants: RR 0.78, 95% CI 0.33 to 1.86; I = 0%; low certainty), cardiovascular death (4 studies, 994 participants: RR 3.02, 95% CI 0.61 to 14.85; low certainty), kidney failure (3 studies, 880 participants: RR 1.36, 95% CI 0.79 to 2.32; I = 0%; low certainty), and doubling of SCr (2 studies, 813 participants: RR 1.14, 95% CI 0.70 to 1.85; I = 0%; low certainty). Compared to ACEi plus ARB, ARB alone has uncertain effects on all-cause death (7 studies, 2607 participants: RR 1.02, 95% CI 0.76 to 1.37; I = 0%; low certainty), withdrawn from treatment (3 studies, 1615 participants: RR 0.81, 95% CI 0.53 to 1.24; I = 0%; low certainty), cardiovascular death (4 studies, 992 participants: RR 3.03, 95% CI 0.62 to 14.93; low certainty), kidney failure (4 studies, 2321 participants: RR 1.15, 95% CI 0.67 to 1.95; I = 29%; low certainty), and doubling of SCr (3 studies, 2252 participants: RR 1.18, 95% CI 0.85 to 1.64; I = 0%; low certainty). Comparative effects of different ACEi or ARB and low-dose versus high-dose ARB were rarely evaluated. No study compared different doses of ACEi. Adverse events of ACEi and ARB were rarely reported. ACEi or ARB may make little or no difference to all-cause and cardiovascular death compared to placebo or no treatment in people with diabetes and kidney disease but may prevent kidney failure. ARB may prevent the doubling of SCr and the progression from microalbuminuria to macroalbuminuria compared with a placebo or no treatment. Despite the international guidelines suggesting not combining ACEi and ARB treatment, the effects of ACEi or ARB monotherapy compared to dual therapy have not been adequately assessed. The limited data availability and the low quality of the included studies prevented the assessment of the benefits and harms of ACEi or ARB in people with diabetes and kidney disease. Low and very low certainty evidence indicates that it is possible that further studies might provide different results.